Strategic Planning as a Determinant of Business Unit Success at AMGPM Ranting Sion Jemaat Poka - Waileruny, Hulawa Theresia; Hadinda, Hadinda (Unram Journal of Community Service, 2024)
The aim of implementing this community service activity is to provide an understanding of the importance ofstrategic planningfor the success of adaptive and sustainable business unitsThe Youth of the Maluku Protestant Church (AMGPM) Zion Branch, Tiberias I, Poka Congregation. Presenting Gen Z who are in the AMGPM Zion Branch, Tiberias I, Poka Congregation, this activity is expected to be the answer to the lack ofeducation related to strategic planning, seeing more than 34% who failed to run a business. This activity is in the form of socialization on topics raised according to the theme "Creating an Adaptive Generation Z in the Digital Era”, specifically onstrategic planning. The average satisfaction of this activity is very good with the number of presentations very satisfied and satisfied at 96.6%. Thus, this activity is expected to be an initial collaboration for the implementation of the knowledge transfer process why the younger generation.